DEVELOPMENT OF ARABIC LANGUAGE LEARNING MODULE ON TA'ARUF MATERIAL BASED ON PROBLEM SOLVING TO IMPROVE SPEAKING SKILLS OF 7TH GRADE STUDENTS AT MTsS DARUL ULUM BUDI AGUNG MEDAN - Desi Susanti; Sahkholid Nasution (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
In the context of Arabic language teaching, the limited availability of effective and engaging learning resources can significantly impact students' learning abilities. Seventh-grade students at MTsS Darul Ulum Budi Agung Medan face difficulties in learning Arabic, particularly in improving their maharah kalam (speaking skills), due to ineffective teaching modules and low student interest in learning Arabic. This research aims to develop an Arabic language learning module on ta'aruf (introduction) material based on problem-solving to enhance the maharah kalam of seventh-grade students at MTsS Darul Ulum Budi Agung Medan. This study employs the Research and Development (RnD) method with the ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation. Constructivism theory, designed by Jean Piaget, serves as the theoretical foundation for developing this problem-solving-based Arabic learning module. In this development, the researchers used several research instruments: direct observation, interviews, expert validation, student and teacher response questionnaires, as well as pre-tests and post-tests. The data analysis techniques employed were descriptive analysis to measure the validity of validator assessments and teacher and student responses, and N-Gain analysis to measure the module's effectiveness. The research findings indicate that the developed Arabic learning module has a validity level of 86% in improving students' maharah kalam, categorized as "very feasible" and requiring no revisions. The practicality of the module, based on responses from teachers and students, is 77.5%, classified as "practical." The effectiveness test using the N-Gain method also shows a percentage of 0.53, falling into the "medium" qualification. Based on the research results, it can be concluded that this Arabic learning module is feasible for implementation for seventh-grade students at MTsS Darul Ulum Budi Agung Medan.